Role of ultrasonography in the diagnosis of gall-bladder carcinoma: A boon for low-resource settings - Sachin Khanduri; Aakshit Goyal; Tarim Usmani; Shreshtha Jain; Arun Goyal; Mriganki Chaudhary; Hritik Sharma; Tushar Sabharwal; Santosh Yadav; Shobha Khanduri; Taruna Singh (Asian Journal of Oncology, 2018)
Purpose: The present study was done with an aim to evaluate the usefulness of ultrasonography (USG) in early diagnosis of gall-bladder carcinoma for low-resource settings. Materials and Methods: A total of 264 clinically suspicious cases were enrolled in the study. The patients underwent USG followed by computed tomography (CT). Histopathological specimens were obtained from 208 cases. Final diagnosis was confirmed histopathologically/CT. Sensitivity, specificity, positive predictive, and negative predictive values of USG were calculated. Results: A total of 29 cases were confirmed as gall-bladder carcinoma, 58.6% were diagnosed at advanced stage (Stage III/IV). USG diagnosed 42 cases as neoplastic, however, 24 were true positive and 18 were false positive. USG was 82.8% sensitive and 92.5% specific. The positive and negative predictive values were 57.1% and 97.8%, respectively, diagnostic efficacy was 91.5%. 94.1% advanced stage gall bladder cancers were diagnosed correctly by USG. Sensitivity for early stages was promising (61.9%), however false positive was higher. Cost of USG was nearly five times lesser as compared to that of CT. Conclusion: USG was a useful economical imaging modality for the screening of gall bladder cancer in low-resource settings, especially for advanced stages. However, for early stages too, it seemed useful. We recommend to encourage the use of USG in early detection of gall-bladder carcinoma in socially and economically disadvantaged settings.